(untitled) (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study highlights a challenge that arises in SMP Negeri 2 Tondano specifically the obstacles faced by students in acquiring English language skills particularly in the area of vocabulary proficiency Regarding certain pupils who continue to struggle with comprehension reading and articulating their thoughts in English as a result of inadequate vocabulary proficiency This study was conducted to investigate eighth grade pupils at SMP Negeri 2 Tondano This study seeks to assess whether students who are instructed using the Short Story method exhibit greater mastery of vocabulary compared to those who are taught without employing the Short Story method The study employed a one group pretest posttest design The research design employed a one group pre test and post test design where the pre test was conducted prior to administering the therapy and the post test was conducted after the treatment was administered A test is conducted using the instrument The questions are presented in a multiple choice format The study included a population of 18 students from class VIII SMP Negeri 2 Tondano < p>